Reciprocal interference between Lactobacillus spp. and Gardnerella vaginalis on initial adherence to epithelial cells - Castro, J. (2013)
Bacterial vaginosis (BV) is the most common vaginal disorder in women of child-bearing age. It is widely accepted that the microbial switch from normal microflora to the flora commonly associated with BV is characterized by a decrease in vaginal colonization by specific Lactobacillus species together with an increase of G. vaginalis and other anaerobes. However, the order of events leading to the development of BV remains poorly characterized and it is unclear whether the decrease in lactobacilli is a cause or a consequence of the increase in the population density of anaerobes. Our goal was to characterize the interaction between two Gardnerella vaginalis strains, one of which was isolated from a healthy woman (strain 5-1) and the other from a woman diagnosed with BV (strain 101), and vaginal lactobacilli on the adherence to cervical epithelial cells. In order to simulate the transition from vaginal health to BV, the lactobacilli were cultured with the epithelial cells first, and then the G. vaginalis strain was introduced. We quantified the inhibition of G. vaginalis adherence by the lactobacilli and displacement of adherent lactobacilli by G. vaginalis. Our results confirmed that pathogenic G vaginalis 101 had a higher capacity for adhesion to the cervical epithelial cells than strain 5-1. Interestingly, strain 101 displaced L. crispatus but not L. iners whereas strain 5-1 had less of an effect and did not affect the two species differently. Furthermore, L. iners actually enhanced adhesion of strain 101 but not of strain 5-1. These results suggest that BV-causing G. vaginalis and L. iners do not interfere with one another, which may help to explain previous reports that women who are colonized with L. iners are more likely to develop BV.